FENOMENA LANSIA MENGHAFAL ALQURAN PADA MAJELIS ALQURAN DI KEC.SALIMPAUNG KAB. TANAH DATAR SUMATERA BARAT - Hayati Hayati; Nurhasnah Nurhasnah; Oktarina Yusra (Tamaddun, 2018)
Recitation of the Al-Qur'an in Nagari Lawang Mandahiling, Kec. Salimpaung Kab. Tanah Datar West Sumatra is one of the branches of the Majelis Panjang Al-Qur'an Padang Panjang which is attended by the elderly who are usually known as the second group who are not much involved in intelligence activities such as memorizing the Qur'an. But in this study the researchers found that the elderly who participated in the study of the Al-Qur'an Council had been actively involved in the activities of studying the meaning of the verses of the Qur'an, memorizing and understanding it since 2014. This descriptive qualitative study aims to find out activities, secrets and factors underlying the ability of the elderly who are 60 years old and above in memorizing the Qur'an. Their activities are divided into six parts, namely the tahfidz preparation stage with motivation and tausiyah from the supervisor, then individual activities, daily activities, weekly activities, monthly activities and khataman activities for participants who have memorized one juz and are ready to perform the Qur’an memorization to the supervisor and pilgrims. The number of participants who have studied were six. Even though they have gone through the Khataman activities, this activity is not the end of the Tahfidz activity because they are still required to repeat their Qur’an memorization and increase their memory. The secret and the biggest factor that underlies the achievement of the Qur'anic verses in the elderly are internal factors in the form of the desire for old age to be filled with useful things and great rewards, love of the Qur'an, calm when interacting with the Qur'an and memorizing it, the desire to increase remembrance both in prayer or outside prayer, and faith and belief in the hereafter, in addition to other supporting external factors.